Pengabdian Masyarakat Berbasis Masjid: Integrasi Kegiatan Religi, Sosial, Kesehatan, dan Pendidikan di Desa Lunjuk - Jul Hendri; Cheni Naluri Liberti; Jihan Rahma; Adeka Alpionita; Enni Gustina; Agung Almukramin; Nori Diah Syafitri; Rahmadani Aulia; Intan Wulan Sari; Catur Darma (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service project titled "Community Engagement Based on Mosque: Integration of Religious, Social, Health, and Educational Activities in Desa Lunjuk" addresses critical issues faced by the community, including high rates of stunting among children and the elderly, inadequate educational support, and underdeveloped infrastructure. The primary objective is to enhance community welfare through a comprehensive approach involving health interventions, educational support, and social cohesion activities, all centered around the mosque as a community hub. Methodologically, the project employs a combination of health workshops, educational programs, and social events, including stunting prevention initiatives, Quranic teaching, and community clean-up efforts. Results indicate significant improvements in community health awareness, increased educational engagement, and strengthened social ties. The project effectively utilized mosque facilities to coordinate various activities, leading to improved infrastructure and enhanced community solidarity.